(untitled) (Physical Education, Health and Social Sciences, 2025)
This study investigates grasshopper populations across four desert regions in Pakistan such as Thar, Cholistan, Kharan and Thall focusing on biodiversity, ecological conditions, and rainfall patterns from 2019 to 2022. These research findings reveal a total of 3255 grasshoppers, with the Thar Desert supporting the highest population (1305 individuals) and species richness (10 species), indicative of its favorable ecological conditions. The Shannon-Wiener Index (2.2868) and Simpson’s Diversity Index (0.8969) further highlight Thar’s significant biodiversity compared to Cholistan (1.9598; 0.8555), Kharan (1.5276; 0.7631), and Thall (1.3276; 0.7018). Rainfall analysis using the Standardized Precipitation Index (SPI) reveals notable variability, with the Thar Desert averaging 136.25 mm of summer rainfall and exhibiting a stable SPI, contrasting with the more erratic patterns observed in Kharan and Thall. These results emphasize the Thar Desert’s critical role in biodiversity conservation, providing a foundational understanding for future ecological management strategies. By integrating diverse analytical approaches, this research contributes valuable insights into desert ecosystems, informing targeted conservation efforts essential for sustaining biodiversity amid climate variability.